KEPUNAHAN BAHASA-BAHASA DAERAH: FAKTOR PENYEBAB DAN IMPLIKASI ETNOLINGUISTIS - Henry Tondo (LIPI Press, 2009)
This article tries to explain the language extinction phenomena in Indonesia particularly in accordance with factors that can cause the language extinction and its ethnolinguistic implications. There are some factors that can be identified as the reasons so that many languages are in the threshold of extinction. Those are the effects of major language, bilingual or multilingual community, globalization, migration, intermarriage, natural disaster, lack of appreciation towards ethnic language, lack of communication intensity using ethnic language in many domains, economic, and bahasa. Meanwhile, the language extinction can ethnolinguistically bring some implications. By the extinction of a language it could be the loss of knowledge on the internal aspects of it, that is, its structure. On the other side, it can bring implications to a loss of local knowledge and other cultural wealth of a certain ethnic using the language because they can only be known through the language used by its community, unless the language has been documented and revitalized. Keywords: extinction, ethnic language, ethnolinguistic